Mapping talent development: definition, scope and architecture - Garavan, T. N.; Carbery, R.; Rock, A. (European Journal of Training and Development, 2012)
Purpose: The purpose of this paper is to explore the concept of talent development, define its scope and identify the issues involved in formulating talent development strategies in organisations. Design/methodology/approach: The paper reviews the relatively scant and fragmented literature on talent development processes. Findings: The literature review revealed that talent development is usually discussed as part of a wider talent management process. The literature highlights issues concerning who is the talent to be developed, what competencies should be developed, who drives development, what is the appropriate pace of development and what is the architecture to support the development. Research limitations/implications: The paper is solely theoretical in nature; however, it does identify gaps for further research. Practice implications: The paper raises a number of important questions that should be considered by organisations when they engage in talent development. Originality/value: The paper contributes to a perceived gap in the literature and highlights the issues that come within the terrain of talent development. Paper type: Literature review